2016
DOI: 10.15244/pjoes/60491
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Asthma and Asthma-Related Symptoms Among Adults Exposed to Indoor Environmental Risk Factors: a Comparison between Winter and Summer in Zunyi, China

Abstract: Weather and climate are known to infl uence human health. Seasonal changes of temperature promote alterations in respiratory morbidity and in total and cause-specifi c mortality. Data on the prevalence of asthma and asthma-related symptoms and its disparities between winter and summer in the acid rain-plagued city of Zunyi in southwestern China have not been widely available.In order to describe the epidemiology of asthma and asthma-related symptoms and its prevalence changes between winter and summer, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
1
1
Order By: Relevance
“…Repeated exposure to coal or wood smoke irritates the lungs and increases the risk of developing asthma. This result is similar to Nigeria, Peru, USA and Ethiopia ( Thacher et al, 2013 ; Gaviola et al, 2016 ; Enilari & Sinha, 2019 ; Abebe et al, 2021 ) but inconsistent with the studies done in Colombia, China, India, and Uganda ( Barry et al, 2010 ; Guddattu, Swathi & Nair, 2010 ; Jie et al, 2016 ; Kirenga et al, 2019 ). This variation could be due to difference in the sample size, cooking space, door opening frequency, and duration of exposure to firewood/coal.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Repeated exposure to coal or wood smoke irritates the lungs and increases the risk of developing asthma. This result is similar to Nigeria, Peru, USA and Ethiopia ( Thacher et al, 2013 ; Gaviola et al, 2016 ; Enilari & Sinha, 2019 ; Abebe et al, 2021 ) but inconsistent with the studies done in Colombia, China, India, and Uganda ( Barry et al, 2010 ; Guddattu, Swathi & Nair, 2010 ; Jie et al, 2016 ; Kirenga et al, 2019 ). This variation could be due to difference in the sample size, cooking space, door opening frequency, and duration of exposure to firewood/coal.…”
Section: Discussioncontrasting
confidence: 92%
“…The low avoidance behavior of pets was similar in this study where 93.6% of the pets were allowed to stay in the respondent’s bedroom. This finding was similar to the study done in Finland, China, and Congo ( Jaakkola et al, 2002 ; Takkouche et al, 2008 ; Jie et al, 2016 ; Obel et al, 2017 ; Luo et al, 2018 ). On the other hand, this finding was inconsistent with the study done in Japan which reported that having pets was a protective factor ( Taniguchi & Kobayashi, 2023 ).…”
Section: Discussionsupporting
confidence: 91%
“…The questionnaire used was a modified questionnaire based on the adult questionnaire of the European Community Respiratory Health Survey II (ECRHS II) that has been widely used in different studies ( 21 ). The questionnaire consists of three parts: the first part of the questionnaire is meant to gather the subject’s personal and socio-demographic data; the second part of the questionnaire elicits information on descriptions and determinants of the use of household fuels; and the third part of the questionnaire is meant to gather information regarding the risk factors of health-related complaints and symptoms in the residential environment in the past 3 months.…”
Section: Methodsmentioning
confidence: 99%